Reflections of novice supervisors on research supervision : a case study at a South African university of technology - Jaya, Ziningi Nobuhle; Thembane, Nokukhanya (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Research supervision is a critical process in which a supervisor guides a research student through conceptualising a research idea, preparing a research proposal and ultimately producing a comprehensive dissertation. The role of a research supervisor is essential in ensuring the quality of the research conducted. This paper explores the experiences of novice supervisors at a South African University of Technology (UoT) as they navigate the complexities and challenges of their roles in research supervision. This paper is guided by theory of experiential learning and role identity theory, focusing on the institutional, pedagogical and relational difficulties novice encounter. The reflective narratives of the participants revealed the importance of formal training, careful supervisor selection and stronger student engagement with institutional support services. This work recommends the need for universities to invest in equipping novice supervisors with the necessary skills and resources, and to nurture greater collaboration between academic departments and support services. Such efforts are essential to strengthening supervision practices and enhancing the overall quality of research outputs.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 4, Volume 9, 2025
Keywords: Higher Education; Novice Supervision; Narrative Enquiry; Research Supervision; Supervision Pedagogy; Student Support Services; Supervisors; Education, Higher -- South Africa; Research